Two Giant Planets Orbiting the K Giant Star η Cet. Issue Volume 8:Issue S299(2013) (6th January 2014) - Trifonov, T.; Reffert, S.; Tan, X.; Lee, M. H.; Quirrenbach, A.
Abstract: We present evidence of a new planetary system around the K giant η Cet (HIP 5364, HD 6805, HR 334), based on 124 high-precision optical and infrared radial velocity data, taken at Lick Observatory (Hamilton) and at VLT (CRIRES). The best dynamical fit to the data is consistent with two massive planets ( m 1 sin i ≈2.6 M Jup, m 2 sin i ≈3.3 MJup ) and with periods of P 1 ≈407 days, P 2 ≈740 days. To test the η Cet system's stability we perform ~ 10, 000 dynamical investigations with maximum time spans of 10 8 years. We find that in case of moderate eccentricities, the planets can be effectively trapped in an anti-aligned stable 2:1 mean motion resonance (MMR), very close to the separatrix. A larger non-resonant stable region exists in low-eccentricity parameter space, although less probable than the 2:1 MMR region.